Marketplace Mapping Positioning Analysis Based On Consumer Perception In The City Of Bandung - Arifin Djakasaputra; Juliana Juliana (SEIKO : Journal of Management & Business, 2022)
The research aims to determine the position and factors that influence marketplace mapping based on consumer perceptions in the city of Bandung. The research method is descriptive. Respondents totaled 137 people, who were determined by non-probability sample (based on purposive assessment) and spread across the city of Bandung. Data were analyzed using multidimensional scaling which analyzed 5 marketplaces, 7 attributes and 15 indicators. The results of the study show that the first position of the marketplace is based on the attributes: 1) ease of use, 2) information quality, 3) consumer service, 4) web/application design, 5) process controllability, 6) outcome quality and 7) price is occupied by Sociolla, followed by Tokopedia, Zalora, Lazada and Elevania with eculidean distance. Keywords: Marketplaces, Position maps, multidimensional scaling, Consumers, Perception.